Before and after Netflix? Changes in the production and narratives of serial fiction in Argentina (2013-2022) - Kirchheimer, Mónica (2023)
Argentine serial fiction has lost presence on open television in the country during the last decade. It is a multi-causal phenomenon that, however, finds a milestone in the disruption of global video-on-demand platforms as producers of local fiction as of 2018, a fact that allows us to understand the mutations of Argentine fiction both in terms of production and narratives. The aim of this paper is to describe and analyze the mutations in both dimensions in the period between 2013 and 2022, a time frame that allows a reading before and after the disruption of the platforms. It is based on a mixed methodological design that combines the evolution of market data with the analysis of fictional narratives. The conclusions highlight the central finding of the work: the extinction of serial fiction from the open television screen, and its recreation from other formats and thematic and narrative keys on large video platforms.